PENGEMBANGAN MATERI AJAR KETERAMPILAN MENGKRITISI INFORMASI TENTANG TOKOH BERBASIS KAHOOT PADA SISWA KELAS XII MAN 1 MEDAN - Manurung , Marshanda; Theresya Hutabarat , Rani; Lorensia Sihombing , Agni; Harianja , Romatua; Isabella Tarigan, Melinda; Hutagalung , Trisnawati; Azizah, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students of grade XII of MAN 1 Medan still have difficulty in critiquing information about figures, especially in assessing the accuracy of data, the author's point of view, and the credibility of sources. The teaching materials used previously were textual and teacher-centered so they did not optimally support higher-order thinking skills (HOTS). This study aims to develop teaching materials for the skills of critiquing information about figures based on Kahoot using the ADDIE development model. The research method used is research and development (R&D) involving Indonesian language teachers and grade XII students as trial subjects. The validity of the product was assessed by material experts and media experts. The validation results showed a very valid category with a very feasible category. Thus, the interactive teaching materials based on Kahoot developed through the ADDIE model are proven to be valid and effective in improving the skills of critiquing information about figures in grade XII students of MAN 1 Medan.